Spatiotemporal patterns of maritime trade between China and Maritime Silk Road: Evidence from a quantitative study using social network analysis. (June 2022) - Mou, Naixia; Wang, Chunying; Yang, Tengfei; Ren, Haonan; Zhang, Lingxian; Xu, Huanqing; Liu, Wenbao
Abstract: Automatic Identification System (AIS) sensor, as a new navigation instrument, provides the possibility for mining the real situation of marine transportation. To find more interesting conclusions from a new perspective, we use AIS sensor trajectory data to explore maritime trade of containers, bulk and tanker between China and Maritime Silk Road (MSR) countries from two perspectives of time and space, and we demonstrate that: (1) In comparison with bulk and tanker market management, China's container market is more reasonable. And congestion in China's coastal ports caused excessive loading and unloading pressure on some ports, especially Hong Kong Port, Zhanjiang Port, and Zhenhai Port, etc. Additionally, there is an interesting phenomenon in bulk and tanker trade: export in the morning and import in the afternoon; (2) The polarization of China's foreign trade is severe. China is prone to trade with countries with high status in the maritime network. In addition, China's tanker import is highly dependent on Russia and the Middle East, which leads to insufficient capacity to address supply chain disruption. Therefore, the research results could provide the scientific basis for China to create opportunities and seek breakthrough points in the new situation.